Estudio del mercado laboral de egresados de Medicina Familiar en Tabasco, México (2018)
The study of the labor market and the perception of the postgraduate studies of graduates from the specialty of family medicine of the Mexican Social Security Institute (IMSS) in Tabasco, allowed a cross-sectional descriptive investigation. From the universe of 201 graduates of the Specialty of Family Medicine, a survey sample of 103 graduates (51%) was determined.Among the results obtained, 59% of the graduates were between 30 and 39 years of age. The group of women predominated with 57%, compared to the group of men with 43%. The majority of the graduated doctors were married (57%), and the Juárez Autonomous University of Tabasco (UJAT) was found as the main university institution, with 66% provenance. 90% worked with clinical care functions in their current job and 96% were very satisfied with the training received. 48% consider that the knowledge acquired has served them to a high degree for professional performance, with the profile of graduates mostly married women between 30 and 39 years of age, coming from the UJAT degree in Surgery, labor-related to the health sector in clinical-care operative activities and currently satisfied with the work they carry out and with the academic training they received.